2016
DOI: 10.1002/2016jb012810
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale grain boundary channels in fracture cement enhance flow in mudrocks

Abstract: Hydrocarbon production from mudrock or shale reservoirs typically exceeds estimates based on mudrock laboratory permeability measurements, with the difference attributed to natural fractures. However, natural fractures in these reservoirs are frequently completely cemented and thus assumed not to contribute to flow. We quantify the permeability of nanoscale grain boundary channels with mean apertures of 50–130 nm in otherwise completely cemented natural fractures of the Eagle Ford Formation and estimate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In any laboratory study of fracture generation, there is always the question of which fractures were generated experimentally, which were generated during core retrieval and handling, and which were generated in situ in the subsurface. Distinguishing among these different types of fractures, even with high‐resolution images, is extremely difficult [e.g., Landry et al ., ]. In our adsorption experiments, we see evidence of deformation in pores smaller than 100 nm, and the SEM images do indicate fractures intersecting those pores.…”
Section: Discussionsupporting
confidence: 49%
“…In any laboratory study of fracture generation, there is always the question of which fractures were generated experimentally, which were generated during core retrieval and handling, and which were generated in situ in the subsurface. Distinguishing among these different types of fractures, even with high‐resolution images, is extremely difficult [e.g., Landry et al ., ]. In our adsorption experiments, we see evidence of deformation in pores smaller than 100 nm, and the SEM images do indicate fractures intersecting those pores.…”
Section: Discussionsupporting
confidence: 49%
“…It is generally accepted that the sealing of fibrous veins keeps up with fracture opening, such that little or no fracture porosity is present during the growth process (Bons et al, 2012). Landry et al (2016) noted that despite the low porosity of mineral fills, they could nonetheless represent sites of enhanced permeability, relative to the host mudrocks. In any case, the nature of the permeability-transient and long-lasting-of mineralized fractures in mudrocks is still largely unresolved.…”
Section: The Nature Of Fracture Sealingmentioning
confidence: 99%
“…A sample mean was calculated based on 1–38 single grain boundary mean apertures (Figure 3c). Because core retrieval and handling can cause microfracturing and dilation of preexisting microfractures and grain boundaries (Landry et al., 2016), we only measured apertures of partially open grain boundaries containing intact cement bridges that completely traverse the grain boundary, thus ascertaining that the apertures are representative of in situ subsurface conditions. The exception are grain boundaries in barite that are generally unbridged.…”
Section: Methodsmentioning
confidence: 99%
“…This does not rule out that stress release during exhumation and possibly during core retrieval affects and possibly widens grain boundaries. Landry et al (2016) defined textural criteria to distinguish grain boundaries widened or formed by stress release from grain boundaries largely unaffected by stress release. They found that mating unbridged grain boundaries may have formed by stress release.…”
Section: Table 2 Occurrences Of Grain Boundary and Bridging Cement Te...mentioning
confidence: 99%
See 1 more Smart Citation